Increased poly-beta-hydroxybutyrate (PHB) chain length by the modulation of PHA synthase activity in recombinant Escherichia coli - Sang, Jun Sim; Snell, KD; Kim, BW; Rha, CK; Sinskey, AJ (Kluwer Academic Publishers, 2001)
A second promoter (P1) was inserted to the PHA (poly-beta-hydroxyalkanoate) operon (pSP2) of Esherichia coli DH5alpha with an optimal E. coli ribosome binding site and a trc strong promoter (pSJS1) to obtain poly-beta-hydroxybutyrate (PHB) with long chain length. When the inducer, IPTG was added to the culture at 0.4 mM, the average molecular weight was 1.1 x 10(6) Da. However, an even greater increase of the PHB average molecular weight to 2.5 x 10(7) Da was observed without IPTG being added.